2014
DOI: 10.15361/1984-5529.2014v42n2p101-107
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação multivariada da composição fenólica de cachaças envelhecidas em diferentes barris de madeira

Abstract: ResumoEste estudo objetivou avaliar a composição fenólica de cachaças envelhecidas em barris construídos de carvalho, jequitibá, castanheira, amburana, bálsamo, jatobá e louro-canela, empregando Análise de Componentes Principais (ACP). Os teores de compostos fenólicos foram centrados na média e submetidos à ACP. Os resultados indicaram que a cachaça envelhecida em castanheira (36 meses), carvalho (48 meses) e louro-canela diferiram das demais por possuirem um elevado teor de ácido gálico, ácido elágico e eugen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…These values are acceptable (32,33) and are close to those obtained by Aquino et al The predominance of certain phenolic compounds was observed in the beverage stored in each type of cask: a predominance of vanillic acid, coumarin and 4methylumbelliferone in the cachaça stored in the amburana cask; a predominance of gallic acid, phenol, syringic acid and syringaldehyde in the balsam cask; a predominance of gallic acid, vanillic acid and syringaldehyde in the oak cask; a predominance of gallic acid and syringaldehyde in the jatoba cask; and a predominance of vanillin and syringic acid in the cachaça stored in the peroba cask. These predominances corroborate some studies found in the literature, but they do not corroborate others (6,8,13,14,31,37). Dias et al (8) showed that ellagic acid and vanillic acid predominated in cachaça stored in oak barrels after six months of aging; vanillin and ellagic acid predominated in a balsam barrel; vanillic acid and sinapaldeído predominated in the amburana barrel; and coniferaldehyde predominated in the jatoba barrel.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…These values are acceptable (32,33) and are close to those obtained by Aquino et al The predominance of certain phenolic compounds was observed in the beverage stored in each type of cask: a predominance of vanillic acid, coumarin and 4methylumbelliferone in the cachaça stored in the amburana cask; a predominance of gallic acid, phenol, syringic acid and syringaldehyde in the balsam cask; a predominance of gallic acid, vanillic acid and syringaldehyde in the oak cask; a predominance of gallic acid and syringaldehyde in the jatoba cask; and a predominance of vanillin and syringic acid in the cachaça stored in the peroba cask. These predominances corroborate some studies found in the literature, but they do not corroborate others (6,8,13,14,31,37). Dias et al (8) showed that ellagic acid and vanillic acid predominated in cachaça stored in oak barrels after six months of aging; vanillin and ellagic acid predominated in a balsam barrel; vanillic acid and sinapaldeído predominated in the amburana barrel; and coniferaldehyde predominated in the jatoba barrel.…”
Section: Resultsmentioning
confidence: 61%
“…The predominance of certain phenolic compounds was observed in the beverage stored in each type of cask: a predominance of vanillic acid, coumarin and 4‐methylumbelliferone in the cachaça stored in the amburana cask; a predominance of gallic acid, phenol, syringic acid and syringaldehyde in the balsam cask; a predominance of gallic acid, vanillic acid and syringaldehyde in the oak cask; a predominance of gallic acid and syringaldehyde in the jatoba cask; and a predominance of vanillin and syringic acid in the cachaça stored in the peroba cask. These predominances corroborate some studies found in the literature, but they do not corroborate others . Dias et al .…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13] A brief description of works that present the separation of aged cachaças by the wood used in the maturation process using different analytical and chemometric methods is shown in Table 1. [14][15][16][17][18][19][20][21][22][23] The following unsupervised exploratory methods: principal component analysis (PCA) and hierarchical cluster analysis have been used in combination with high-performance liquid chromatography coupled with diode array detection, 15,18,20 sensorial analysis, 21 electrospray ionization mass spectrometry, 22 and electronic spectroscopy. 23 Supervised classification methods have also been used: Rodrigues and co-workers presented models using artificial neural networks, k-nearest neighbor, linear discriminant analysis, quadratic discriminant analysis, multilayer perceptron, and support vector machine coupled to a computer vision system and chemical information, obtaining accuracy up to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of cachaça obtained after the aging process in different woods makes it an attractive field of study 9‐13 . A brief description of works that present the separation of aged cachaças by the wood used in the maturation process using different analytical and chemometric methods is shown in Table 1 14‐23 …”
Section: Introductionmentioning
confidence: 99%